2021
DOI: 10.3389/fendo.2021.713961
|View full text |Cite
|
Sign up to set email alerts
|

Neuromedins NMU and NMS: An Updated Overview of Their Functions

Abstract: More than 35 years have passed since the identification of neuromedin U (NMU). Dozens of publications have been devoted to its physiological role in the organism, which have provided insight into its occurrence in the body, its synthesis and mechanism of action at the cellular level. Two G protein-coupled receptors (GPCRs) have been identified, with NMUR1 distributed mainly peripherally and NMUR2 predominantly centrally. Recognition of the role of NMU in the control of energy homeostasis of the body has greatl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 125 publications
(210 reference statements)
2
37
0
Order By: Relevance
“…In addition, our results also showed that the levels of NMU expression were different in sheep intestinal segments. Studies have demonstrated that NMU secreted by enteric nerves has multiple functions [ 53 55 ]. However, their microenvironments and functions are different in different segments, such as the colonization flora, the composition of the mucosal epithelium, and local immunity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our results also showed that the levels of NMU expression were different in sheep intestinal segments. Studies have demonstrated that NMU secreted by enteric nerves has multiple functions [ 53 55 ]. However, their microenvironments and functions are different in different segments, such as the colonization flora, the composition of the mucosal epithelium, and local immunity [ 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that NMU secreted by enteric nerves has multiple functions [ 53 55 ]. However, their microenvironments and functions are different in different segments, such as the colonization flora, the composition of the mucosal epithelium, and local immunity [ 55 ]. Therefore, in healthy sheep intestine, the differences of NMU expression levels in each segment is a display for their physiological differences.…”
Section: Discussionmentioning
confidence: 99%
“…Neuromedin U is found in multiple parts of the body (including the testis, ovary, thyroid, spleen, placenta, and adipose tissue) and cell types (endothelial cells, keratinocytes, and lymphocytes), but is especially concentrated in the pituitary gland and gastrointestinal tract (3,4) (Figure 1). In-depth research into the molecular mechanisms has revealed many important roles of NMU, including regulating feeding behavior, balancing energy metabolism, controlling circadian rhythms, regulating immunity, maintaining bone formation, and combating tumors and anxiety (2,(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…NMU has been implicated in a variety of physiological processes, such as inflammation, stress, nociception, energy homeostasis, reproduction, bone remodeling, and cardiovascular and gastrointestinal functions. 2 Two G-protein-coupled receptors (GPCR) for NMU (NMUR1 and NMUR2) have been identified and correspond to the orphan receptors FM3 and FM4, respectively. 3 NMUR1 has the highest expression in peripheral tissues particularly the GI tract, pancreas, uterus, and testes but has also been reported in peripheral nerve terminals.…”
Section: ■ Introductionmentioning
confidence: 99%